INVESTIGACIÓN ACCIÓN PARTICIPATIVA Y SU APORTE EN LA INNOVACIÓN EDUCATIVA - CARBO MARTILLO, MELANY TERESA (2024)
Participatory action research is a research approach that brings together academics and activists to co-create knowledge and social change together according to the author Kemmis (2015) cited by (Cornish et al., 2023), it is also a collaborative, iterative effort, often open and unpredictable, prioritizing the experience of those experiencing a social problem and using systematic research methodologies to generate new knowledge. The following project called Participatory Action Research and its contribution to Educational Innovation has the general objective of determining how PAR contributes to educational innovation in the E.U. Aurora Estrada Ayala from the city of Babahoyo, 2024. In this study, a descriptive methodological approach was used, allowing a detailed analysis of the practices, perceptions and changes experienced by teachers and teaching managers in relation to educational innovation. Furthermore, the documentary research design was used as a valuable methodology to contextualize and substantiate the contribution of Participatory Action Research (PAR) in educational innovation. This approach involved the critical review and systematic analysis of relevant documentary sources, such as institutional reports, academic records, curricula, and other documents that may shed light on the implementation and outcomes of PAR. For the development of the project, 3 teaching managers and 12 teachers were taken as a statistical sample, the same ones who served as the object of study to obtain relevant and interesting results and conclusions about the problem.